2000
DOI: 10.1007/bf02345748
|View full text |Cite
|
Sign up to set email alerts
|

Dipole location errors in electroencephalogram source analysis due to volume conductor model errors

Abstract: An examination is made of dipole location errors in electroencephalogram (EEG) source analysis, due to not incorporating the ventricular system (VS), omitting a hole in the skull and underestimating skull conductivity. The simulations are performed for a large number of test dipoles in 3D using the finite difference method. The maximum dipole location error encountered, utilising 27 and 53 electrodes is 7.6 mm and 6.1 mm, respectively when omitting the VS, 5.6 mm and 5.2 mm, respectively when neglecting the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 25 publications
6
60
1
1
Order By: Relevance
“…Several researchers investigated the dipole location error due to skull conductivity perturbation (Awada et al 1998, Pohlmeier et al 1997, Laarne et al 2000, and Vanrumste et al 2000. Awada et al (1998) used 2D finite element method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several researchers investigated the dipole location error due to skull conductivity perturbation (Awada et al 1998, Pohlmeier et al 1997, Laarne et al 2000, and Vanrumste et al 2000. Awada et al (1998) used 2D finite element method.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, Laarne et al (2000) found that the average dipole location error was about 7.5 mm and 6.5 mm when 19 electrode and 58 electrodes were used respectively. Vanrumste et al (2000) used a large number of test dipoles and a 3D volume conductor to investigate the dipole location error due to the higher skull conductivity of head model used in the forward problem than that in the inverse problem. They found that the location error of most test dipoles was between 5 mm and 20 mm, and the maximum errors were33.4 mm and 28.0 mm for 27 and 53 electrodes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In EEG source problem, neural sources are reconstructed inside the brain based on electric potential measurements around the scalp, and it is well known that the inverse solution depends strongly on the accuracy of discretized head geometry [2,4,7,8,16,39,49,54] and the accuracy of electric conductivity modelling of different tissues [3,47,25,48,34,50,51]. The head features can be extracted, to some extent, by using multi-modal imaging (computed tomography / diffusion magnetic resonance imaging), for example.…”
Section: Introductionmentioning
confidence: 99%